Examining EFL vocabulary learning motivation in a demotivating learning environment. (April 2017) - Tanaka, Mitsuko
Abstract: Situated in a demotivating learning environment, this study examined the roles of motivation and peers in EFL vocabulary learning. The participants were 155 science and engineering students in Japan. They took a vocabulary test and responded to a questionnaire based on the self-determination theory and peer engagement/disengagement in learning. The results of six multiple stepwise regression analyses showed that: (1) to enjoy and value learning is vital to develop a larger vocabulary size; (2) perceived autonomy is important in cultivating the enjoyment and value of learning in learners' minds; (3) perceived competence plays a decisive role in motivating and demotivating learners; and (4) whereas motivated peers have little impact on learners' motivation in a demotivating learning environment, demotivated peers have a negative influence. These findings reveal the malleability of peer influences as well as crucial factors for successful EFL vocabulary acquisition in a demotivating learning context.